2017
DOI: 10.7150/ntno.19796
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Vaccines Adopting Virus-like Features for Enhanced Immune Potentiation

Abstract: Synthetic nanoparticles play an increasingly significant role in vaccine design and development as many nanoparticle vaccines show improved safety and efficacy over conventional formulations. These nanoformulations are structurally similar to viruses, which are nanoscale pathogenic organisms that have served as a key selective pressure driving the evolution of our immune system. As a result, mechanisms behind the benefits of nanoparticle vaccines can often find analogue to the interaction dynamics between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 223 publications
(249 reference statements)
1
110
0
3
Order By: Relevance
“…45 In addition to V-ATPase, inhibitors of other host factors may be contemplated for improving the design of antiviral nanoparticles. Given the recent rise in immunomodulatory nanoparticle development, 46,47 antiviral nanoparticles may also incorporate innate immune modulators to further enhance treatment potency. This study, for the first time, demonstrates the therapeutic promise of nanoparticulate V-ATPase inhibitors in a mouse model of influenza virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…45 In addition to V-ATPase, inhibitors of other host factors may be contemplated for improving the design of antiviral nanoparticles. Given the recent rise in immunomodulatory nanoparticle development, 46,47 antiviral nanoparticles may also incorporate innate immune modulators to further enhance treatment potency. This study, for the first time, demonstrates the therapeutic promise of nanoparticulate V-ATPase inhibitors in a mouse model of influenza virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of antigens in nanoparticles can be achieved by encapsulation (physical entrapment) or by conjugation (covalent functionalization) (21). Studies have demonstrated that nanoparticles could protect the native structure of antigens from proteolytic degradation and/or improve antigen delivery to antigen-presenting cells (APCs) (31).…”
Section: Nanoparticles An Alternative Approach To Conventional Vaccinesmentioning
confidence: 99%
“…Over the last decade, a number of nanoparticles have been designed to mimic respiratory viruses in terms of size, shape and surface property in order to target NALT as well as to raise humoral and cellular immune responses (21,55,56). First, beside a nanoparticle size of 20-200 nm in diameter to match the size of most respiratory viruses, nanoparticles should be preferably positively charged.…”
Section: Nanoparticles and The Respiratory Tract Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 While the SC route of delivery has been widely employed for nanoparticle vaccines in preclinical development, 1115 conventional vaccines used in the clinic are typically administered via the intramuscular (IM) route, 16,17 presumably due to the “depot” effect for prolonged vaccine delivery. 18 Therefore, with our long-term goal set on clinical translation of the nanovaccine technology, we have sought to address the following three questions in this current study: (1) to determine whether SC route of administration offers a superior site of nanodisc vaccination than the IM route; (2) to assess systemic and local safety profiles of nanodisc vaccination; (3) to thoroughly evaluate the therapeutic efficacy of vaccine nanodiscs in combination with ICBs for treatment of advanced, established tumors.…”
mentioning
confidence: 99%